Design for sustainability: contributions of reflective design to the emotional longevity of fashion products (DAPesquisa, 2021)
In this article, through bibliographic research, the objective is to explore the contributions of the concept of reflective design (NORMAN, 2008) in the expectation of longevity of fashion products, in search of a more sustainable scenario through the awakening of pleasant emotions and the creation of affective bonds between users and their clothes. Considering that part of the socio-environmental problem comes from the impacts of production and consumption caused by the fashion system, the idea of developing products that can last longer according to their emotional value and that, therefore, will contribute to the deceleration of cycles disposal and replacement. In this context, based on the theory of Emotional Design (JORDAN, 1999; DESMET, 2002; NORMAN, 2008), reflective design strategies are developed that can assist in the design of projects with a focus on facilitating emotionally lasting experiences.
Keywords: Fashion design; User-centered system design; Sustainability